Savants and diplomats: The politics of commemoration at the Berthelot centenary, 1927. (25th May 2020) - Fox, Robert
Abstract: The grandeur of the celebration to mark the centenary of Marcellin Berthelot's birth in 1927 surpassed even that of the Pasteur centenary 4 years earlier. The explanation lies in the contemporary state of international relations in science, following the exclusion since 1919 of Germany and the other Central Powers from the International Research Council and its associated disciplinary unions. In the face of growing demands for the post‐war ostracism to end, the Berthelot centenary became far more than a purely scientific commemoration. Diplomacy also loomed large in a range of activities aimed at furthering the wider aim of Franco‐German reconciliation while also affirming the place of France as a leading international force in chemistry. Berthelot's son Philippe, a diplomat, played a key role in promoting this union of diplomatic and scientific interests and helping to give it material expression through the establishment in Paris of a global centre for the discipline, the Maison de la Chimie.